Plan de negocios para la creación del Departamento de Producción para el sector agrícola y pecuario en el Gobierno Autónomo Descentralizado del cantón Calvas. 2014 - Cueva Santorum, Carlos Ernesto (2014)
The research has as objective the elaboration of the business Plan to the creation of the Production Department to the agricultural and livestock of the Autonomous Decentralized Government of the Calvas town. The purpose of the Department is to work with public and private entities managing programs and projects that allow re-active the primary sector of the town that is the agriculture and livestock, thus applying new alternatives of production The project consists of a general diagnostic of the actual situation of the town and its economic development. To gather the information was done a field research, which applied 351 surveys the same that were distributed in different parishes of the town. The information obtained gives to know the products that are produce in big and small scale. Also, it was detected the weaknesses of the agricultural producers and the lack of support of the competent institutions. Consequently, it was proposed the creation of the Department with their respective functions and competent; besides it details the lines of action by means of the strategic plan; and the budget of investment for the operation.